Design of Vehicle Charger for Pure Electric Vehicle Based on MATLAB Simulation. (November 2020) - Zhu, Xiaqing; Kong, Lingyu; Yang, Xinjun; Xu, Ya
Abstract: In this paper, the basic principle of the on-board charger of electric vehicle is studied and analyzed, and the design scheme of vehicle charger with two-stage transformation structure is proposed. The former converter adopts boost active power factor correction circuit to improve power factor and reduce total harmonic distortion; the latter adopts phase shifted full bridge ZVS inverter circuit to realize electrical isolation and DC / DC conversion. According to this scheme, a 2kW vehicle charger is designed. The charging mode adopts three-stage charging method to charge lithium battery pack, and the three-stage charging is simulated. The results are consistent with the requirements of three-stage charging curve.